Exploring the Impact of Mandarin Language Proficiency, Networking, and Popularity on Career Support in Medan, Indonesia - Rizky Lubis; Clairine Jessica; Elly Romy; Kiki Goslim; Wenny Wenny; Cynthia Hualangi (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2024)
This study examines the influence of Mandarin language competency, networking, and popularity on career support in Medan City. A quantitative methodology was utilized to collect data via questionnaires distributed to 30 participants, which were subsequently evaluated using validity and reliability assessments, descriptive statistics, and linear regression. The results demonstrate that skills in Mandarin and networking do not substantially impact career support; instead, popularity exerts a considerable influence. When evaluated collectively, the three variables substantially influence career support. The results indicate that while Mandarin language proficiency and networking do not substantially aid job advancement, popularity is vital. The comprehensive analysis highlights the significance of Mandarin language proficiency, relationship cultivation, and popularity in enhancing career prospects in Medan.